2005
DOI: 10.1007/s00210-004-1016-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HER-2 by three independent targeting strategies increases paclitaxel resistance of SKOV-3 ovarian carcinoma cells

Abstract: Current treatment options for ovarian cancer, which is one of the most widespread gynecological malignancies, are limited, mainly because patients with advanced-stage disease often develop resistance to chemotherapeutics. In breast cancer cells, several studies suggest that overexpression of the human epidermal growth factor receptor-2 (HER-2) leads to increased resistance against certain, but not all cytotoxic drugs. In ovarian carcinoma, conflicting data on the correlation of HER-2 expression and tumor cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…A large cooperative group trial demonstrated an estimated disease-free survival advantage of 18% for sequential rather than concurrent chemotherapy and tamoxifen treatment when given in the adjuvant setting (18). In addition, inhibition of HER2 by trastuzumab first, but not in the reverse order, increased paclitaxel resistance of ovarian cancer cells (19). Since several anti-IGF1R antibodies are being evaluated in phase I /II/III clinical trials, some in combination with cytotoxic chemotherapy, it is be important to determine the optimal schedule for the antibodies in combination with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A large cooperative group trial demonstrated an estimated disease-free survival advantage of 18% for sequential rather than concurrent chemotherapy and tamoxifen treatment when given in the adjuvant setting (18). In addition, inhibition of HER2 by trastuzumab first, but not in the reverse order, increased paclitaxel resistance of ovarian cancer cells (19). Since several anti-IGF1R antibodies are being evaluated in phase I /II/III clinical trials, some in combination with cytotoxic chemotherapy, it is be important to determine the optimal schedule for the antibodies in combination with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the haematological cancer cells obtained from bone marrow had a much lower proliferation rate than the metastatic cancer cells obtained from ascites or pleural fluids. The effectiveness of various chemotherapeutic agents, including doxorubicin [20], paclitaxel [13,21] and cisplatin [13,22], may depend on cell proliferation to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Dual antibody therapy was the most potent resulting in a significant reduction in tumor volume by day four [19]. The relationship between HER2 status and chemotherapy resistance in ovarian cancer has also been examined; sensitivity to paclitaxel was increased approximately 70-fold in SKOV3 ovarian cancer cells expressing high levels of HER2 and, in a later study, treatment with trastuzumab resulted in increased resistance to paclitaxel [20,21].…”
Section: Preclinical Datamentioning
confidence: 98%